Case report: Splenic inflammatory pseudotumor-like follicular dendritic cell sarcoma (IPT-like FDCS): a trial of immunotherapy and review of the literature - Resnick, K. A.; Monroe, C.; Siddiqi, I.; Tam, E. (Frontiers in Oncology, 2024)
Inflammatory pseudotumor-like follicular dendritic cell sarcoma (IPT-like FDCS) is a rare malignancy with fewer than 150 cases in the literature. IPT-like FDCS follows an indolent course with most cases definitively managed with surgical resection. We present a case of IPT-like FDCS with multiple recurrences with a trial of immunotherapy. The patient initially presented with splenic involvement requiring splenectomy, subsequently recurring in the liver requiring hepatic resections. Afterwards, there was recurrence with pelvic/small bowel involvement for which treatment was trialed with ipilimumab and nivolumab. The patient progressed despite dual immune checkpoint inhibitor therapy requiring a small bowel resection. To date, this is the first case of immunotherapy use in IPT-like FDCS. Therefore, more evidence is needed to support additional treatments in recurrent IPT-like FDCS after resection.